STUDI PENERAPAN STRATEGI SEGMENTASI PASAR, TARGET PASAR DAN PENEMPATAN POSISI GUNA PENINGKATAN JUMLAH KONSUMEN PADA HOTEL KARTIKA WIJAYA BATU - Eni Maryati, Wahyu (Jurnal Teknik Industri, 2001)
Market segmentationh ave purpose to devide plural customersi nlo the same marketsegmentationF. rom this segment,m arket sharet hat will be served dependingt o the segmentt hat givemaximum profit for Kartika Wijaya Hotel Batu.The methodu sedi n this researchis usingc lustera nalysisw ith SPSSp rograma s a help.T hesecondm ethodt hat be usedi s caracteristiacn alysism ethodo f customeres achs egmenut singc rossT absanalysisa nd the third methodu singp references tructurea nalysism ethodo f segmenut sing Thurstone'scase analysis.In customers egmentatioann alysisu singc lastera nalysisc an got 5 segments4.. of 5 balancesegmentfso rmedc ustomer'sp rofile caracterislice very segmenbt asedo n demografvi ariatesb, ehaviors,and advantagesA. nd from customer'sp references truclure concludet hat the prize that have beend ecidedby companyim portanat spect/s a tributeso f customer.